2020
DOI: 10.1002/oby.22682
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Life‐Course Obesity and Frailty in Older Adults: Findings in the GAZEL Cohort

Abstract: ► Frailty is a predictor of poor health outcomes among older adults. ► Although weight loss is part of frailty, previous studies demonstrated that aged individuals with obesity are more likely to be frail compared with aged individuals without obesity. ► The impact of life-course obesity on the risk of frailty in old age remains poorly described.What does this study add?► In a cohort of older adults followed for 26 years, we showed that the duration of obesity influences the risk of frailty: the longer the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 37 publications
3
20
0
2
Order By: Relevance
“…Our sample presented a status of overnutrition according to different nutritional markers, including obesity according to BMI, waist circumference, body fat percentage, and biochemical markers. While BMI alone does not seem to be a suitable measure for assessing the risk of frailty [38], in populations with high caloric intake there is evidence of an association between obesity and frailty [39], and BMI trajectories have revealed that both long-term obesity and onset of obesity in late adulthood were associated with frailty [40]. Central obesity, as assessed by waist circumference, was high in both groups, although the body fat percentage was slightly lower in the prefrail/frail group.…”
Section: Discussionmentioning
confidence: 99%
“…Our sample presented a status of overnutrition according to different nutritional markers, including obesity according to BMI, waist circumference, body fat percentage, and biochemical markers. While BMI alone does not seem to be a suitable measure for assessing the risk of frailty [38], in populations with high caloric intake there is evidence of an association between obesity and frailty [39], and BMI trajectories have revealed that both long-term obesity and onset of obesity in late adulthood were associated with frailty [40]. Central obesity, as assessed by waist circumference, was high in both groups, although the body fat percentage was slightly lower in the prefrail/frail group.…”
Section: Discussionmentioning
confidence: 99%
“…A high proportion of undernourished people are frail, and undernutrition leads to weight loss, which can contribute to the frailty syndrome [ 18 ]. At the other end of the spectrum is overnutrition; obesity increases frailty risk [ 19 ], with evidence that the risk of frailty increases with longer duration of obesity [ 20 ]. In terms of body composition, frailty has been associated with higher body fat mass and fat percentage, with low muscle mass and often no association with body mass index (BMI) [ 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Longitudinal studies have also found that obesity predicts the development of frailty [18][19][20][21][22][23][24][25]. For example, a study by Stenholm et al [24] concluded that midlife obesity led to a fivefold increase in the risk of frailty over a 22-year follow up compared to those of normal weight among participants in the Mini-Finland Health Examination Survey.…”
Section: Introductionmentioning
confidence: 99%